Erlotinib-induced complete response in a patient with epidermal growth factor receptor wild-type lung adenocarcinoma after chemotherapy failure: a case report - Vitale, Maria Giuseppa (BioMed Central, 2014)
INTRODUCTION: The efficacy of erlotinib in advanced non-small-cell lung cancer has been demonstrated in several trials, but only two cases of complete and prolonged response in wild-type epidermal growth factor receptor locally advanced lung cancer have been published. CASE PRESENTATION: We discuss a case of a 67-year-old Caucasian man, a former heavy cigarette smoker, with a diagnosis of wild-type epidermal growth factor receptor locally advanced adenocarcinoma. After platinum-based doublet chemotherapy, when a progression of disease had occurred, a second-line therapy with erlotinib was started. We observed a progressive reduction of his lung lesion during erlotinib treatment until there was a complete clinical response. CONCLUSIONS: This case is interesting for the choice of second-line treatment in non-small-cell lung cancer and, moreover, for the possibility of a complete and prolonged response to erlotinib even in patients without the activating mutation of epidermal growth factor receptor.